Sensory processing issue and occupational engagement among children with autism in Genius Kurnia Center, Sentul / Shahrizal Selamat - Selamat, Shahrizal (2020)
Estimated about 42% to 88% of children with autism experience sensory processing issues. This sensory processing problem in autism may affect the child behaviour and functional performance in their context. This study is intended to identify the impaired sensory processing and occupational engagement, the relationship of sensory processing and occupational engagement with demographic profile, and the relationship between sensory processing issues and occupational engagement among children with ASD. Data were collected by using purposeful sampling strategies. Children with ASD (n=l69) from GENIUS Kumia were recruited. Instrument used are the School Companion Sensory Profile and the Short Child Occupational Profile (SCOPE). The research finding indicated that overall, children with ASD appear to experience some degree of processing issues in "avoiding" sensory pattern and appear significant challenge in "communication and interaction skills" in their occupational engagement. Sensory processing issues and activity engagement are also found to be minimal to moderate relationship on demographic profile of the children. The study also concludes that both sensory processing and occupational engagement among children with ASD are interrelated. In other words, if children experience some degree of atypical sensory responses, the child might also experience a great challenge to successfully participate in their occupation of daily living. The correlation coefficients are ranging from (r = - 0.20) to (r = -0.36) indicating fair to moderate correlation between sensory processing and occupational engagement. These sensory processing issues have significant impact on children life which can be seen through their level of engagement in daily life activities.